Integrated analysis and single-cell sequencing of mitochondrial metabolism related gene molecular subtype and diagnostic model in ulcerative colitis - Li Li; Xiaoyao Chen; Tao Li; Bing Sun; Bo Zhang; Weifeng Zhang; Junbo Wu; Meng Cui; Guoliang Wu (PLoS ONE, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease that seriously affects the life expectancy of patients. Although increasingly sophisticated combinations of drugs can alleviate symptoms, 10–20% of patients still do not respond well. Therefore, it is necessary to further explore the pathogenesis and potential biomarkers of UC. Many clues have suggested the important value of mitochondrial metabolism in UC, but its role and related targets need to be further explored. By public database data, we identified differentially expressed mitochondrial metabolism related genes (MMRG) in UC. Subsequently, we identified biomarkers associated with MMRG based on a machine learning approach. After classifying the MMRG-associated molecular subtypes of UC, we comprehensively analyzed the MMRG biomarkers and the relationship between the MMRG molecular subtypes and immune infiltration characteristics. Single-cell sequencing analysis showed significant expression pattern of MMRG signatures in different cell subtypes. qRT-PCR and western blot further confirmed the abnormal expressions of selected genes in vitro. Our findings provided a new perspective on the role of MMRG in UC.